2019
DOI: 10.1101/611681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal theta codes for distances in semantic and temporal spaces

Abstract: The medial temporal lobe (MTL) is known to support episodic memory and spatial navigation, raising the possibility that its true function is to form "cognitive maps" of any kind of information. Studies in humans and animals support the idea that the hippocampal theta rhythm (4-8 Hz) is key to this mapping function, as it has been repeatedly observed during spatial navigation tasks. If episodic memory and spatial navigation are two sides of the same coin, we hypothesized that theta oscillations would also refle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 65 publications
5
51
1
Order By: Relevance
“…A final additional aspect that demands discussion is the absence of distance coding in the hippocampus and entorhinal cortex. This result is surprising because previous studies reported such effect (Theves et al 2019;Solomon et al 2019;Viganò & Piazza 2020). Several discrepancies between these studies and the current one might account for this putative contradiction.…”
Section: The Representation Of Faced Direction In Parietal Cortexcontrasting
confidence: 99%
See 1 more Smart Citation
“…A final additional aspect that demands discussion is the absence of distance coding in the hippocampus and entorhinal cortex. This result is surprising because previous studies reported such effect (Theves et al 2019;Solomon et al 2019;Viganò & Piazza 2020). Several discrepancies between these studies and the current one might account for this putative contradiction.…”
Section: The Representation Of Faced Direction In Parietal Cortexcontrasting
confidence: 99%
“…A more parsimonious explanation might be the fact that the entorhinal cortex, given its anatomical position, is more prone to signal loss, and effects of this kind might be too subtle to be reliably detected and replicated using 3 or 4T magnets. This argument might well also apply to the hippocampus, specifically in light of the results of Solomon et al 2019, that showed a distance effect between words using intracranial electrophysiology, thus with a significantly higher spatial resolution compared to our current one. A more carefully designed experiment addressing this specific question with an ROI approach, in combination with high-field magnets, might be the more accurate way to experimentally solve the issue.…”
Section: The Representation Of Faced Direction In Parietal Cortexmentioning
confidence: 50%
“…Understanding different connectivity relationships for these two oscillations using the associative recognition paradigm may help illuminate separate slow and fast theta networks that explicate regions involved in familiarity versus recollection, especially during retrieval. Certainly, a comprehensive understanding of these oscillations requires further characterization, including contrasts between spatial navigation and verbal memory and updated models of theta generation and propagation accounting for possible slow versus fast theta differences Solomon, Lega, Sperling, & Kahana, 2019). However, our findings support a model by which slow theta oscillatory power increases are necessary for associative memory during item retrieval and as such they constitute direct evidence of a role for these oscillations in recollection.…”
Section: Discussionmentioning
confidence: 49%
“…Chen et al, 2016;Clarke et al, 2018). In particular, recent evidence suggests theta activity in the ATL might be particularly important for coding semantic representations of basic-level objects , which is consistent with evidence that theta activity in the MTL dissociates between different object categories (Kraskov et al, 2007) and tracks the access of semantic knowledge (Ackeren et al, 2014;Bastiaansen et al, 2005;Fuentemilla et al, 2014;Halgren et al, 2015;Solomon et al, 2019;Watrous & Ekstrom, 2014).…”
Section: Introductionmentioning
confidence: 52%